Proceeding of the 2nd International Conference on Tropical Agriculture (Springer International Publishing, 2018)
The proceeding of the 2nd International Conference on Tropical Agriculture (ICTA) is a proceeding to publish papers presented at the corresponding conference held in 26-27 October 2017. The conference was organized by Universitas Gadjah Mada, Indonesia in collaboration with five Faculties including Faculty of Agriculture, Faculty of Animal Science, Faculty of Veterinary, Faculty of Agricultural Technology and Faculty of Forestry. The conference was held with the theme "Integrated and sustainable tropical agriculture with subtheme "Building community socio-ecological resilience to climate change through agricultural innovations." Interest is growing in sustainable agriculture when agriculture has evolved for many years from simple or manual farming to more industrial agriculture. The sustainable agriculture involves the use of productive farming technology that takes advantages of biological resources and process to conserve the environment and enhance public health. Furthermore, sustainable agriculture should include all aspects of sustainable criteria, such as technical, socio-economic, and ecological aspects. This book covers the sustainable tropical agriculture, sustainable tropical animal production and health, sustainable tropical forestry, socio-economic dimension in tropical agriculture and innovative and emerging food technology and management as chapters in this book. The common challenging problems in plant, animal, and fisheries production in the tropic are climate change, inefficiency production system, low technological innovation, decreasing environment quality, and the outbreak risk of pest and diseases. The problems are closely bound to the condition of socio-economic of farmers as the small scale farm is dominant in this area. In addition, post-harvest technology is crucial to maintaining the high quality of the product after on farm production. This book provides the recent research and development on tropical agriculture production systems either for the plant, terrestrial animal and aquatic animal to establish the sustainable agriculture production in the tropic.